2013
DOI: 10.1242/jcs.107805
|View full text |Cite
|
Sign up to set email alerts
|

CORVET and HOPS tethering complexescoordinators of endosome and lysosome fusion

Abstract: SummaryProtein and lipid transport along the endolysosomal system of eukaryotic cells depends on multiple fusion and fission events. Over the past few years, the molecular constituents of both fission and fusion machineries have been identified. Here, we focus on the mechanism of membrane fusion at endosomes, vacuoles and lysosomes, and in particular on the role of the two homologous tethering complexes called CORVET and HOPS. Both complexes are heterohexamers; they share four subunits, interact with Rab GTPas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
479
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 472 publications
(495 citation statements)
references
References 140 publications
(248 reference statements)
14
479
0
2
Order By: Relevance
“…In yeast cells, the HOPS complex is recruited by the active form of RAB GTPase Ypt7/RAB7 to mediate fusion between the prevacuolar compartment membrane and vacuole/lysosome membrane with the assistance of SNARE proteins (16)(17)(18). In Arabidopsis, RAB7/RABG GTPases and a Rab5 homolog Rha1/RABF2a were also involved in vacuolar trafficking of cargo proteins (24)(25)(26).…”
Section: Atvps41 Is Localized Mainly In the Late Endosomes/pvcs And Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In yeast cells, the HOPS complex is recruited by the active form of RAB GTPase Ypt7/RAB7 to mediate fusion between the prevacuolar compartment membrane and vacuole/lysosome membrane with the assistance of SNARE proteins (16)(17)(18). In Arabidopsis, RAB7/RABG GTPases and a Rab5 homolog Rha1/RABF2a were also involved in vacuolar trafficking of cargo proteins (24)(25)(26).…”
Section: Atvps41 Is Localized Mainly In the Late Endosomes/pvcs And Tmentioning
confidence: 99%
“…In yeast, studies on vacuolar assembly identified a tethering complex, the homotypic fusion and vacuolar protein sorting (HOPS) complex, which consists of four core subunits and two HOPS-specific subunits, Vps41p and Vps39p (15). Vps41p promotes membrane fusion between late endosomes and lysosomes by working as an effector of Ypt7, a GTP-binding protein (16)(17)(18). Loss of Vps41p function led to failure of vacuole membrane fusion and production of fragmented vacuoles (19).…”
mentioning
confidence: 99%
“…17,18 CORVET promotes the maturation of early to late endosomes in yeast but remains poorly characterized in animals. Metazoan HOPS and CORVET tethering complexes are speculated to share 5 subunits: the homologs of CG32350/Vps11, Vps16, dor/Vps18, car/Vps33, and Vps39.…”
Section: Resultsmentioning
confidence: 99%
“…Metazoan HOPS and CORVET tethering complexes are speculated to share 5 subunits: the homologs of CG32350/Vps11, Vps16, dor/Vps18, car/Vps33, and Vps39. 17,18 We have recently shown that autophagosomes accumulate when any one of the 6 HOPS subunits are lost in Drosophila, and the levels of both lipidated and nonlipidated forms of Atg8a and ref(2)P/p62 are massively upregulated not only in Vps16A-null mutants but also in hypomorphic CG32350/Vps11-or lt/Vps41-mutant animals. 11,19 Importantly, CG32350/Vps11-mutant larvae also developed slower than control animals, which could be again partially rescued by the expression of Rheb (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation